Feedlot performance of Angus and Brahman x Angus steers during cold weather - Boyles, S.; Riley, Jack G.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Straightbred Angus steers gained .21 lb/day faster than Brahman x Angus steers during a 184-day winter feeding trial. Angus steers had a higher yield grade. more fat thickness at 12th rib, and graded 90% Choice. Brahman x Angus steers were 40 days younger at slaughter, had more carcass weight/day of age and larger loin eyes, but only graded 10% choice. There was no difference in feed efficiency.
Keywords: Beef; Feedlot performance; Carcass weight; Yield grade